PRODUCTION OF SPACE, TRANSFORMATIONS OF CAPITALISM AND THE REAL ESTATE STRATEGIES OF RETAIL COMPANIES - Pereira, Cláudio Smalley Soares (Mercator, 2020)
This paper aims to analyze the current transformations of commercial capital in contemporary capitalism. In light of the dynamics of globalization, retail commercial capital has changed its actions and strategies, based on the prevailing logic of the functioning of the capitalist economy in the current period. The study examines the global expansion of retail, as well as its territorial consequences, and gives particular emphasis to the role of financialization and real estate business in these dynamics. Finally, we highlight how both foreign and domestic retail companies began to view real estate investment as a means of obtaining profitability that contributes to economic reproduction. Keywords : Contemporary Capitalism, Commercial Capital, Retail, Real Estate Strategy.